(untitled) (International journal of artificial intelligence, 2025)
The foundation of organizational decision-making and external reporting is financial accounting. However, significant negative outcomes, such as regulatory penalties, tax misstatements, and financial mismanagement, can result from accounting errors, both procedural and judgmental. Through a structured literature review, practitioner perspectives, and real-world case studies, this paper examines common accounting errors. The study provides specific prevention recommendations and identifies ten primary error types that affect businesses of various sizes. The use of cutting-edge accounting software and the significance of professional oversight are emphasized.